A Review of Theoretical Perspectives on CSR Among Family Enterprises. Issue 3 (September 2019) - Chalkasra, Lolita Shaila P. Safaee; Rivera, John Paolo R.; Basuil, Dynah Avigail T.
Corporate Social Responsibility (CSR) practices vary across international, regional and national contexts. It depends on variations in regulatory frameworks and global institutionalization, which views enterprises in a positive light when they adhere to global standards of social responsibility. Enterprises are not only seen as economic agents but also social actors with respective social responsibilities. We review theoretical perspectives on CSR among family enterprises and imply the type of CSR that a family enterprise may pursue depending on the different orientations that prescribe behaviour and motivation, which is dependent on organizational structure and size.